Revolutionary biomarkers: Transforming the Future of Parkinsonism Diagnosis - Govind, Govind; Shrivastav, Sonika; Agarwal, Prabhat; Yadav, Anjali; Manish, Manish; Chaturvedi, Sushma (Journal of Neonatal Surgery, 2025)
Introduction: After Alzheimer's disease, Parkinson's disease (PD), which is distinguished by gradual motor impairment, is the subsequent prominent neurodegenerative movement disease. Differentiating PD from other Parkinsonian disorders is challenging due to overlapping symptoms. Objective: This review aims to provide a comprehensive overview of current developments in the search for biomarkers for Parkinson's disease (PD), with a focus on their utility in differentiating PD from other Parkinsonian syndromes. Methods: A thorough analysis of existing literature was conducted also explores relevant research articles, clinical trials, and meta-analyses to discuss their applications in early detection, differential diagnosis, and monitoring disease progression. Results: α-Synuclein Seed Amplification Assays (SAAs) in CSF show great promise for early and accurate PD diagnosis due to their high sensitivity and specificity. GFAP, while less specific, can be valuable for monitoring neurodegeneration severity. CSF levels of Aβ42, p-tau, and t-tau can help predict cognitive impairment in PD, particularly in differentiating PDD from PDMCI. YKL-40 can differentiate as well as activation of macrophages and microglia. Integrating non-motor symptom assessments with objective biomarker measurements may improve the accuracy of early PD diagnosis. Conclusion: CSF biomarkers, particularly α-Synuclein SAAs, hold significant potential for improving the diagnosis and management of PD. While individual biomarkers have limitations, combining them with clinical assessments and auxiliary methods can enhance diagnostic accuracy. Further research, including longitudinal studies and validation in diverse cohorts, is needed to fully realize the clinical utility of these biomarkers in predicting treatment response and understanding the underlying pathophysiology of PD.